Comunicação em rede, novos agentes socializadores e recepção práticas culturais: o consumo de Internet em lan-houses na periferia de São Paulo - Bredarioli, Claudia Maria Moraes (2008)
In a scenario formed by the globalization process emerged from the technological progress, the Internet access in private places (lan-houses) portrays a movement that apparently begins to create new paths in the search for economic and social inclusion of youths from poor neighbourhoods of large Brazilian cities. To identify in what way or until what point attending lan-houses leads to this process of inclusion is one of the challenges that communication researchers face. These places have become socializing agents that must be studied in particular because they lack characteristics of formally organized institutions such as school, family and Church; and therefore allow the appearance of new cultural practices brought by these contemporary mediatic supports which take over new social urban spaces. In this study we attempt to further understand the issue by elaborating a cultural and mediatic consumption map of this youth – which the results point out the existence of a large mass of functional Internet users, still unable to completely grasp new technologies or take advantage of day-to-day possibilities on the net in the constitution of citizenship.